2020
DOI: 10.1126/sciadv.aba2578
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity intervention enhances immune regulation and health-associated commensal microbiota among daycare children

Abstract: As the incidence of immune-mediated diseases has increased rapidly in developed societies, there is an unmet need for novel prophylactic practices to fight against these maladies. This study is the first human intervention trial in which urban environmental biodiversity was manipulated to examine its effects on the commensal microbiome and immunoregulation in children. We analyzed changes in the skin and gut microbiota and blood immune markers of children during a 28-day biodiversity intervention. Children in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
180
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(203 citation statements)
references
References 40 publications
4
180
1
1
Order By: Relevance
“…During this period, adolescents could use support in reinforcing their mental health [ 70 ]. In light of these results and earlier research findings, it is important to endorse contact with nature as it not only enhances well-being [ 71 ], but also may have effects on immune regulation [ 72 ] and intelligence [ 73 ].…”
Section: Discussionmentioning
confidence: 88%
“…During this period, adolescents could use support in reinforcing their mental health [ 70 ]. In light of these results and earlier research findings, it is important to endorse contact with nature as it not only enhances well-being [ 71 ], but also may have effects on immune regulation [ 72 ] and intelligence [ 73 ].…”
Section: Discussionmentioning
confidence: 88%
“…Importantly, urban green space exposure can result in transmission of environmentally-derived bacteria to the skin and airways ( 21 ). Furthermore, a recent study showed that transfer of bacteria from biodiverse environments enhanced immunoregulatory pathways in children ( 38 ). Consequently, environments with different levels of bacterial diversity may affect the potentiality of bacterial exposure levels and transfer loads, warranting further research.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the key topics in this field cover early life ( Tamburini et al, 2016 ), mechanisms of colonization resistance against pathogens ( Buffie and Pamer, 2013 ; Kim et al, 2017 ), and stability and individuality of adult microbiota ( Mehta et al, 2018 ), and its associations with diseases, diet, medication, and lifestyle in various populations across the globe ( Segata et al, 2011 ; Schmidt et al, 2018 ; Cullen et al, 2020 ). Moreover, the research focus is shifting toward considering the role of genetics and environment ( Org et al, 2015 ; Roslund et al, 2020 ), as well as of diet ( Singh et al, 2017 ), and to translate this knowledge into microbiota-based clinical solutions ( Lynch et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%